"I Learned Who I Am": Young People Born From Genocide Rape in Rwanda and Their Experiences of Disclosure. Issue 5 (September 2018) - Hogwood, Jemma; Mushashi, Christine; Jones, Stuart; Auerbach, Carl
Sexual violence was systematically used to terrorize thousands of Tutsi women and girls during the 1994 Rwandan genocide, infecting many with HIV and resulting in thousands of children born as a result of rape. Now these children are young adults; they are asking questions about their parentage and are often faced with challenging parent–child relationships, discrimination, stigmatization, and identity issues. As a result, there is a need for them to understand more about their birth histories. Through community counseling groups, mothers of these young people have been supported to disclose to their child about their birth histories. This study aims to understand how the young people experienced the disclosure and how this affected their sense of identity. Semistructured interviews were conducted with 10 young people and analyzed using interpretative phenomenological analysis. Three subordinate themes and eight subthemes begin to describe the complex and difficult process of learning about a new identity, the process of reconstructing a positive identity, and reworking family relationships as a result of the knowledge acquired. The young people appreciated knowing about their birth histories despite the painful emotions. Recommendations are made as to how these young people and their families can be better supported.